2016
DOI: 10.1371/journal.pone.0157956
|View full text |Cite
|
Sign up to set email alerts
|

Chronic IL-6 Administration Desensitizes IL-6 Response in Liver, Causes Hyperleptinemia and Aggravates Steatosis in Diet-Induced-Obese Mice

Abstract: High-fat diet-induced obesity (DIO) is associated with fatty liver and elevated IL-6 circulating levels. IL-6 administration in rodents has yielded contradictory results regarding its effects on steatosis progression. In some models of fatty liver disease, high doses of human IL-6 ameliorate the liver steatosis, whereas restoration of IL-6 in DIO IL-6-/- mice up-regulates hepatic lipogenic enzymes and aggravates steatosis. We further examined the effects of chronic low doses of murine IL-6 on hepatic lipid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
1
14
1
1
Order By: Relevance
“…In these animals, a compensatory increase in many other cytokines has been reported . In contrast, low‐dose application of murine IL‐6 in mice leads to hepatic steatosis . Subchronic IL‐6 administration in IL‐6‐deficient mice exacerbated hepatic steatosis by increasing lipogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these animals, a compensatory increase in many other cytokines has been reported . In contrast, low‐dose application of murine IL‐6 in mice leads to hepatic steatosis . Subchronic IL‐6 administration in IL‐6‐deficient mice exacerbated hepatic steatosis by increasing lipogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…(21) In contrast, low-dose application of murine IL-6 in mice leads to hepatic steatosis. (44) Subchronic IL-6 administration in IL-6-deficient mice exacerbated hepatic steatosis by increasing lipogenesis. (45) Importantly, neutralization of IL-6 with neutralizing antibodies in HFD-fed mice improved glucose tolerance and ameliorated liver fat content.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1β secreted from adipose tissue can regulate fat–liver crosstalk in obesity (Nov et al , ). IL‐6 administration can elevate fat liver content and aggravated steatosis in HFD‐induced obese mice despite the expression of lipogenic genes being suppressed (Gavito et al , ). A clinical trial found that ω‐3 PUFA supplementation reduced the expression of IL‐6, IL‐8, TNFα and toll‐like receptor 4 in adipose tissue of obese pregnant women (Haghiac et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…(B-C) Average energy intake and food intake (n = 6 independent experiments in different rats). (D) Subregions of rats identified by pDXA [64]. Fat mass % and lean mass % of the rats in the different groups were measured.…”
Section: Resultsmentioning
confidence: 99%
“…(C-D) The mRNA expression levels of NPY and POMC in the hypothalamus. The levels of MC3R and MC4R protein were determined [64]. Data are the mean ± SEM.…”
Section: Resultsmentioning
confidence: 99%